Las catedrales de España - Pillement, Georges (1953)
Incluye breves monografías sobre las catedrales de: Almería, Astorga, Badajoz, Baeza, Burgo de Osma, Ciudad Real, Ciudad Rodrigo, Coria, Guadix, Jaca, Jaén, León, Lugo, Mondoñedo, Murcia, Orense, Orihuela, Oviedo, Plasencia, Santander, Santiago de Compostela, Seo de Urgel, Solsona, Tuy, Vitoria y Zamora.